GE_GERICHTE A/1912/2013 vom 26. September 2013 - GE Cour de justice (2013)
Saisie; revendication; contestation; péremption; déni de justice; plainte irrecevable. | LP.17; LP.32.2; LP.33; LP.107; LP.108